wintersuntime
  • wintersuntime
Can someone be nice enough to help me with this question .>> 3x-10=2 what's x ?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
x = 4 3 x 4 = 12 - 10 = 2
anonymous
  • anonymous
3x=12 x=12/3 x=4
wintersuntime
  • wintersuntime
yes I was right thanks

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

wintersuntime
  • wintersuntime
need help on one more
anonymous
  • anonymous
Yup :) Ask away
wintersuntime
  • wintersuntime
3x+6=x+2
anonymous
  • anonymous
3x=x-4 2x=-4 x=-4/2 x=-2
anonymous
  • anonymous
x = -2
anonymous
  • anonymous
Simplifying 3x + 6 = x + 2 Reorder the terms: 6 + 3x = x + 2 Reorder the terms: 6 + 3x = 2 + x Solving 6 + 3x = 2 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6 + 3x + -1x = 2 + x + -1x Combine like terms: 3x + -1x = 2x 6 + 2x = 2 + x + -1x Combine like terms: x + -1x = 0 6 + 2x = 2 + 0 6 + 2x = 2 Add '-6' to each side of the equation. 6 + -6 + 2x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 2 + -6 2x = 2 + -6 Combine like terms: 2 + -6 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2

Looking for something else?

Not the answer you are looking for? Search for more explanations.